Changing business from the inside out : a treehugger's guide to working in corporations - Mohin, Timothy J. (BK business book., 2012)
Tim Mohin argues that environmentalists can do as much good for the earth working inside the corporate system as by protesting from the outside. This book outlines how to work in Corporate Social Responsibility (CSR), either as a new career, of as a leader in a CSR initiative.